Enhancement of bioelectricity generation from treatment of distillery wastewater using microbial fuel cell. Issue 2 (25th September 2017) - Naina Mohamed, Samsudeen; Thota Karunakaran, Radhakrishnan; Manickam, Matheswaran
Abstract : Distillery wastewater is an important potential sources for electricity generation using Microbial Fuel Cell (MFC) because of it has high content of organic waste and can be easily degraded. This study investigated the effect of feed pH and buffering conditions on electricity production and treatment efficiency using distillery wastewater as a substrate in MFC. The anodic chamber was operated with diluted distillery wastewater (4000 ± 20 mg COD/L) at various pH between 5.4 and 10 while the cathode chamber was maintained at pH 7.5. The MFC peak power density of 168 mW/m 2 (580 mA/m 2 ) with COD, color and TDS removal efficiency of 68.2, 26.4, and 15.4%, respectively was achieved at pH 8. Cyclic voltammetry revealed that an exoelectrogenic activity of microorganism was significantly influenced with respect to pH. The effect of buffering salts in the anolyte on MFC performance was also investigated. When the system operating with borate buffer, highest power density of 194.7 mW/m 2 (624 mA/m 2 ) at 100 Ω was achieved. The result indicated that alkaline condition (pH 8) and borate buffer was favored for obtaining maximum power generation and treatment efficiency from distillery wastewater in the MFC. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 663–668, 2018